(untitled) (Scottish Historical and Archaeological Internet Reports, 2003)
The areas of survey were as follows: the cemetery and church area, the Bu Lawn, the West Field and the East Field. Survey failed to find any trace of the Round Church but did identify the remains of the 19th-century church. Features identified in the Bu Lawn were problematic and the related data issues are discussed. Features linked to possible cultivation and a burnt mound were identified in the West Field. The East Field contained features possibly linked to cultivation, boundary features, a possible building and a possible dump of ferrous material.